I’m Sorry, I’ve got Something to Do: A Study of EFL Learners’ Refusal Strategies - Murti Ayu Wijayanti (Journal of English Language and Culture, 2017)
The present study aimed at investigating the English refusal strategies chosen by EFL learners in one public university in Banten regarding social status. A Discourse Completion Task consisting of two situations was employed to gather the data. The data taken were classified and analyzed based on Beebe, et.al (1990). The research result showed that most EFL learners chose indirect strategies to refuse by giving reasons and explanation followed by statements of regret. In relation with social status, in giving indirect refusals as the addition of giving reasons and regret, the EFL learners tended to provide alternatives to the request given by their friends or equal status. However, they tended to provide positive opinions to refuse a request given by someone with higher status. Keywords: refusals, request, social status